2010
DOI: 10.1055/s-0030-1248261
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Affects Mitochondrial Function

Abstract: The aim of the present study was to examine mitochondrial function in cells from persons with subclinical hypothyroidism and euthyroid controls. The participating persons were examined clinically and had basal oxygen consumption (VO(2)) determined. The concentrations of thyroid hormones and thyrotropine stimulating hormone were determined, and mitochondrial function in isolated mononuclear blood cells was examined by enzymatic methods [citrate synthase activity (CS)] and by flow cytometry (mitochondrial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…In either situation, hemithyroidectomy induces a decrease in the metabolic state to which the individual was adapted preoperatively. We have previously demonstrated increased mitochondrial processes, and thereby increased MMP, in PBMCs of patients with subclinical hypothyroidism compared with controls [4], and the present study has reproduced these results in a hemithyroidectomized patient group, using two different measures of MMP. Subclinical hypothyroidism is associated with an increased risk of coronary heart disease [13,14], and recent studies have demonstrated an association between low thyroid function within the euthyroid range and various cardiovascular risk markers [15,16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In either situation, hemithyroidectomy induces a decrease in the metabolic state to which the individual was adapted preoperatively. We have previously demonstrated increased mitochondrial processes, and thereby increased MMP, in PBMCs of patients with subclinical hypothyroidism compared with controls [4], and the present study has reproduced these results in a hemithyroidectomized patient group, using two different measures of MMP. Subclinical hypothyroidism is associated with an increased risk of coronary heart disease [13,14], and recent studies have demonstrated an association between low thyroid function within the euthyroid range and various cardiovascular risk markers [15,16].…”
Section: Discussionsupporting
confidence: 82%
“…Respiratory gas analysis and volume measurements were performed with a canopy connected by a triple V (flow/gas sensor) to an Oxycon Pro apparatus (Jaeger Oxycon Champion, Breda, The Netherlands), as previously described [4]. The relation between V˙ O 2 and MMP was examined, and we observed a significant correlation between measurements of V˙ O 2 and the MMP of MTG-stained PBMCs (r = 0.46, p = 0.03), indicating that V˙ O 2 reflects inner mitochondrial membrane O 2 consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even low-normal free thyroxin levels in patients with euthyroidism have been associated with insulin resistance (22,23). Thyroid disease induces mitochondrial dysfunction (24)(25)(26)(27), and statins reduce levels of coenzyme Q10, a component of the electron transport chain involved in the process of ATP generation (28), also leading to mitochondrial dysfunction as well as causing reduced insulin release and pancreatic b-cell failure and contributing to the development of DM (29)(30)(31)(32). Downregulation of GLUT4 in adipocytes has also been shown to be a result of statin treatment, an effect that has been explained in terms of reduced isoprenoid biosynthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that SCH can lead to energy expenditure and affect cell functions (29). Thyroid functions are determined through metabolic parameters.…”
Section: Discussionmentioning
confidence: 99%